Development and Establishment Educational and Research Pillars of the Higher Education Institution - Usmonov, Botir (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
A good higher education system is required for overall prosperity of a nation. A tremendous growth in the higher education sector had made the researchers of higher education institutions complex. Many studies reveal that the integration of science helps to overall growth of the higher education. This study has been undertaken to identify the unity of scientific and educational processes aimed at improving the efficiency of the economy. The various factors that contribute to these educational and research areas were identified. An educational - scientific industrial complex model was derived and validated.